2019
DOI: 10.1177/0951629819875522
|View full text |Cite
|
Sign up to set email alerts
|

Why differentiated integration is such a common practice in Europe: A rational explanation

Abstract: With Brexit imminent, the debate on the need for differentiated integration (DI) by means of opting-out has gained new momentum. At the same time, non-member states decide to adopt European Union (EU) rules as exemplified by the European Neighbourhood Policy. In light of these opposing observations, we examine the EU’s disposition to supply DI. We outline the strategic interactions of the EU member states or non-members in the context of two forms of DI: opting-out and inducing-in. In the case of opting-out, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…While research on the causes of DI has reached its scientific maturity, there has been much less research on the consequences of DI (Burk & Leuffen, 2019;Gänzle et al, 2019). Recently, Brexit gave a new momentum to this strand of research, as the UK's decision to exit the EU in spite of the opt-outs it enjoyed (Holzinger & Tosun, 2019) may suggest that DI paves the way to (differentiated) disintegration (Leruth et al, 2019b;Schimmelfennig, 2018). So far, existing empirical evidence has shown that treaty law and secondary legislation follow similar differentiation logics (Duttle et al, 2017;Schimmelfennig & Winzen, 2020).…”
Section: The Causes and Consequences Of DImentioning
confidence: 99%
“…While research on the causes of DI has reached its scientific maturity, there has been much less research on the consequences of DI (Burk & Leuffen, 2019;Gänzle et al, 2019). Recently, Brexit gave a new momentum to this strand of research, as the UK's decision to exit the EU in spite of the opt-outs it enjoyed (Holzinger & Tosun, 2019) may suggest that DI paves the way to (differentiated) disintegration (Leruth et al, 2019b;Schimmelfennig, 2018). So far, existing empirical evidence has shown that treaty law and secondary legislation follow similar differentiation logics (Duttle et al, 2017;Schimmelfennig & Winzen, 2020).…”
Section: The Causes and Consequences Of DImentioning
confidence: 99%
“…The EU represents a unique experiment of differentiation (Schimmelfennig and Winzen, 2020), yet whether this differentiation is of a permanent nature, or involves member states all going towards the same direction in integration, albeit with different speeds still remains to be seen (Kolliker, 2001;Lord, 2015;Ganzle and et.al., 2020;Leruth and et.al., 2019). Similarly, one might conceptualize the different trajectories for non-member states opting into the EU policies as a permanent status of associating oneself with the EU (Gstohl, 2015) and/or as a preparatory trajectory for eventual accession sometime in the future (Holzinger and Tosun, 2019). External differentiated integration for non-EU members involves temporal alignment to EU policies and territorial inclusions-such as security cooperation, participation in the Single Market, free trade agreements, Customs Union or participation in the Schengen zone for third parties and policy optins such as the adoption of EU regulations in electricity, telecommunications, and education.…”
Section: External Differentiated Integrationmentioning
confidence: 99%
“…It is important to note, however, we still assume classical bargaining dynamics in the Council before the vote is taken. 4) We use the terminology that is by now common in the literature on DI (Leuffen et al 2013;Holzinger and Tosun 2019). That is, the first stage in Moravcsik's model corresponds to the formation of the demand for differentiation by a national government; the second step corresponds to the supply-side of differentiation and its delivery after successful negotiations in the Council of Ministers for Agriculture.…”
Section: The Liberal Intergovernmentalist Frameworkmentioning
confidence: 99%
“…Analytical theories to explain DI (e.g. Leuffen et al 2013;Jensen and Slapin 2012;Holzinger and Tosun 2019) and systematic empirical evidence (e.g. Winzen 2016;Duttle et al 2017) are a rather recent phenomenon.…”
Section: Introductionmentioning
confidence: 99%